A new mutation in the human lipoprotein lipase gene causing familial hyperchylomicronaemia. Issue 4 (August 1997) - Anwar, R; Puntis, J W; Markham, A F
Abstract : Lipoprotein lipase plays a major role in the regulation of lipid metabolism. The enzyme acts to hydrolyse triglycerides, providing free fatty acids for energy generation or storage, thus affecting the maturation of circulating lipoproteins. Biochemical and molecular analyses were performed on two siblings of consanguineous Pakistani origin, presenting with hyperchylomicronaemia, which revealed that the disorder resulted from lipoprotein lipase deficiency. Molecular analysis of the lipoprotein lipase gene has revealed a novel homozygous mutation, leucine to proline at amino acid residue 303, within the amino terminal domain of the protein.